THE NECESSITY OF USING AL-RIWAYAH BI AL-LAFDZ: AN EFFORT TO PROTECT THE HADITH NABAWI - Azhar, M. Fahmi (Universum, 2023)
al-Riwayah in the study of hadith is one of the most important aspects because it involves the transmission of the words of the prophet from time to time. The responsibility for matters relating to the authenticity of a hadith lies with the rawi. The riwayah of hadith is divided into two madzhab. First, madzhab of al-riwayah bi al-lafdz and second, madzhab riwayah bi al-ma’na. The ulama agree that al-riwayah bi al-lafdz is the main thing, while the meaning is as relief (tarhis). al-al-riwayah bi al-lafdz is a rawi who narrates the hadith obtained from his teacher in accordance with the pronunciation received. This riwayah by the ulama is used as a form of caution and guard against the hadith of the Prophet from things that damage and falsify it, this is so that the hadith remains authentic, all the pronunciations come from the Prophet Muhammad.